Faktor-Faktor Yang Mempengaruhi Pengambilan Keputusan Terhadap Pelaksanaan Triase Di IGD Rumah Sakit Murni Teguh Sudirman Jakarta - Kusuma, Meilida Eka; Simatupang, Lenny Lusia (Universitas Murni Teguh, 2025)
The emergency department is one of the service units in a hospital that provides first aid andis the first route for entry of patients with emergency conditions. There are several nursingfactors that can influence the accuracy of carrying out triage, namely, the skills and personalcapacity of the implementing nurse. Skills in this case include education level, work experience,and age, while personal capacity includes knowledge and motivation. The objective of thisstudy is to find out the factors that influence decision making regarding the implementation oftriage in the ER at Murni Teguh Sudirman Hospital, Jakarta. The research design uses acrosssectional approach in quantitative research. This research is explanatory research. Thesample in this research was 31 respondents using nonprobability sampling. The results of theresearch obtained a chi-square test between workload and decision making in implementingtriage in the emergency room at Murni Teguh Sudirman Hospital. The p value was 0.014, whichmeans that there was an influence between workload and decision making in implementingtriage in the emergency room at Murni Teguh Sudirman Hospital. It is concluded that there is asignificant relationship between decision making and the implementation of triage in the ER atMurni Teguh Sudirman Hospital, Jakarta.